The THE STUDY ON GLOBALIZATION AND ITS EFFECTS ON BUSINESS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Factors and motives are combined with knowledge, means and methods, talents and predispositions to generate the current liberal, capitalistic and economic activity. The unavoidable process of globalization and commercial operations reflect undertakings that have both success and failure potentials because of the reduced boundaries and openness of the world. Successful and reliable commercial initiatives, with their ultimate objective being financial happiness, limiting risk and establishing long-term experiences in order to continue a firm in a certain environment are unquestionably the focus of these considerations. It has been a continuous tale in worldwide business for at least three centuries. As long as civilization has existed in its more or less structured form, so has the global economy. Since the Industrial Revolution, global economic integration has been unstoppable. Because business and profits do not recognize boundaries, national and cultural unique qualities, when a mutual advantage is identified, a commercial link is made quickly